The scientific publications of AIFM members in 2015–2019: A survey of the FutuRuS working group. (August 2021) - Placidi, Lorenzo; Castriconi, Roberta; Rancati, Tiziana; Lecchi, Michela; Fusi, Franco; Russo, Paolo; Cavedon, Carlo; Fiorino, Claudio; Garibaldi, Cristina
Highlights: Peer-reviewed papers published in the years 2015–2019 by AIFM members were surveyed. A total of 1210 papers, mostly in the field of Radiation Oncology (48%) were found. The most represented journal was Physica Medica, with 15% of papers. This survey constitutes a basis to promote future AIFM scientific activities. This survey will be useful for comparison with other countries, first within Europe. Abstract: Purpose: Within the Italian Association of Medical Physics and Health Physics (AIFM) working group "FutuRuS" we carried out a survey regarding the number of the peer-reviewed articles by AIFM members. Methods: We surveyed papers published in the years 2015–2019. Data extracted from Scopus included information regarding authors, title, journal, impact factor (IF), leading or standard authorship by AIFM members, keywords, type of collaboration (monocentric/multicentric/international), area of interest [radiation oncology (RO), radiology (RAD), nuclear medicine (NM), radioprotection (RP) and professional issue (PI)] and topics. Results: We found 1210 papers published in peer-reviewed journals: 48%, 22%, 16%, 6%, 2 and 6% in RO, RAD, NM, RP, PI and other topics, respectively. Forty-seven percent of the papers involved monocentric teams, 31% multicentric and 22% international collaborations. Leading authorship of AIFM members was in 56% of papers, with a corresponding IF equal to 52% of the total IF (3342, IFmean = 2.8, IFmax = 35.4). The most represented journal was Physica Medica, with 15% of papers, while a relevant fraction of IF (54%) appeared in clinically oriented journals. The number of papers increased significantly between 2015 and 2016 and remained almost constant in 2017–2019. Conclusions: This survey led to the first quantitative assessment of the number and theme distribution of peer-reviewed scientific articles contributed by AIFM members. It constitutes a ground basis to support future AIFM strategies and promote working groups on scientific activity of medical physicists, and to build the basis for rational comparison with other countries, first of all within Europe.